Analysis of The Impact of on-Street Parking on Traffic Performance on One-Way Streets (Case Study: Gajah Mada Street, Bima City - Isnandi Isnandi; Sharwanda Asfarina; M. Deta Zulfikar Rahman (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The continuous growth of population and motor vehicle ownership in Bima City has not been balanced by adequate road infrastructure development, causing traffic congestion, especially on strategic one-way national roads such as Jalan Gajah Mada, where on-street parking activities reduce the effective road width and disturb traffic flow. This study aims to identify the traffic volume passing through Jalan Gajah Mada and to analyze the influence of on-street parking on the traffic performance of this one-way road segment. A quantitative descriptive method was applied, collecting primary data through three days of field surveys covering morning, midday, and afternoon periods, then analyzed using the Indonesian Highway Capacity Manual (MKJI) 1997 to calculate traffic volume, side friction, free flow speed, road capacity, degree of saturation, and level of service. Results indicate the highest peak-hour volume reached 877.1 pcu/hour on Monday afternoon, dominated by motorcycles, with parking and stopping vehicles (PSV) contributing the largest weighted side friction frequency (200 of 417.3), classifying the segment as medium side friction. This condition reduced free flow speed to 42.12 km/hour and road capacity to 2,161 pcu/hour, producing a degree of saturation of 0.41 with level of service B, indicating stable flow despite noticeable parking-related friction. In conclusion, on-street parking measurably affects traffic performance, though current conditions remain within tolerable capacity. Local authorities are recommended to enforce stricter parking regulations, including peak-hour on-street parking prohibition and provision of off-street alternatives, to prevent future performance decline. Further research should extend observation periods and include forecasting simulations.